Surgical Management of Penoscrotal Filariasis by Reconstructive Penoscrotoplasty: An Experience from a Tertiary Healthcare Centre - Aditya Sharma; Ritika Khanna; Shashi Prakash Mishra; Ram Niwas Meena; Seema Khanna; Rahul Khanna (Amrita Journal of Medicine)
Chronic lymphedema has a number of etiological causes that affect the lymphatic drainage system. It is characterized by the gradual buildup of protein-rich fluid in the subcutaneous tissue. Any of the body components may be involved, and the causes may vary from congenital to acquired. Lymphedema and subcutaneous tissue thickening are characteristics of external genital elephantiasis. As a result, the skin has a pachyderm-like look. For the sufferer, this pathology is invalidating. Often, reconstructive surgery is the only option for restoring the external genitalia’s appearance and functionality. We report a case series of patients who presented with giant penoscrotal filariasis and were successfully managed with reconstructive penoscrotoplasty.